English Reading Comprehension of 9th Grade Students in Iceland - Ólöf Hildur Egilsdóttir 1961- (2012)
This study focuses on how reading comprehension in English has evolved among primary school students in Iceland from the years 1983. 146 9th grade students in 4 primary schools in Reykjavik, Iceland retook standardized reading comprehension examinations from the years 1983, 1997 and 2008 and their results were analyzed, compared and correlated with the original test taker’s results. The 2012 test takers performed marginally higher in the 1983 standardized examination than the original test takers, but scored lower than the original 1997 test takers, and scored even lower on the 2008 examination. The results showed that reading comprehension is on the decline which did support the tentative hypothesis proposed in the study. Test results correlated with text length and difficulty in the examinations. The longer and more academic the text, the worse the performance of the test takers.